Odpowiedzi

2010-03-16T17:46:40+01:00
4x - 3x = 5-3
x = 2

5x+3x= 7-2
2x = 5/2
x = 2.5

3(x-1)=0
3x - 3=0
3x= 0 +3
3X = 3/ 3
X = 1


-6(x+1)=24
-6X -6 = 24
-6X = 30 / -6
X = -5


-7(x-2)=3x-1
-7X + 14 = 3X - 1
-9X = -14 - 1
-9X = -15 / -9
X= -15/-9
Najlepsza Odpowiedź!
2010-03-16T17:47:08+01:00
A) 4x-3= 3x+5
4x-3x=5+3
x=8
b) 5x+2= 7-3x
5x+3x=7-2
8x=5
x=5/8
c) 3(x-1)=0
3x-3=0
3x=3
x=1
d)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30
x=30/-6
x=-5
e) -7(x-2)=3x-1
-7x+14-3x=-1
-10x=-1-14
-10x=-15
x=15/10
x=1 i 5/10=1 i 1/2
f) 4(x-1)= 6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=10/-2
x=-5
pozdrawiam:)
1 5 1
2010-03-16T18:01:28+01:00
A)4x-3=3x+5
4x-3x=5+3
x=8
b)5x+2=7-3x
5x+3x=7-2
8x=5/podzielić na 8
x=0.625
c)3(x-1)=0
3x-3=0
3x=0+3
3x=3/podzielić na 3
x=1
d)-6(x+1)=24
-6x-(-6)=24
-6x=24-6
-6x=18/podzielić na -6
x=3
e)-7(x-2)=3x-1
-7x-14=3x-1
-7x-3x=-1+14
-10x=13/podzielić na -10
x=-1.3
f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/podzielić na -2
x=-5